Monotherapy With Anti-CD70 Antibody Causes Long-Term Mouse Cardiac Allograft Acceptance With Induction of Tolerogenic Dendritic Cells - Zhao, Jing; Que, Weitao; Du, Xiaoxiao; Fujino, Masayuki; Ichimaru, Naotsugu; Ueta, Hisashi; Tokuda, Nobuko; Guo, Wen-zhi; Zabrocki, Piotr; de Haard, Hans; Nonomura, Norio; Li, Xiao-Kang (Frontiers in Immunology, 2021)
Allograft rejection has been an obstacle for the long-term survival of patients. CD70, a tumor necrosis factor (TNF) family member critically expressed on antigen-presenting cells and strongly but transiently up-regulated during lymphocyte activation, represents an important co-stimulatory molecule that induces effective T cell responses. We used a mouse heterotopic cardiac transplantation model to evaluate the effects of monotherapy with the antibody targeting mouse CD70 (FR70) on transplantation tolerance and its immunoregulatory activity. FR70-treated C3H recipient mice permanently accepted B6 fully mismatched cardiac allografts. Consistent with the graft survival, the infiltration of CD8+ T cells in the graft was reduced, dendritic cells were differentiated into a tolerogenic status, and the number of regulatory T cells was elevated both in the graft and the recipient’s spleen. In addition, naïve C3H given an adoptive transfer of spleen cells from the primary recipients with FR70 treatment accepted a heart graft from a matching B6 donor but not third-party BALB/c mice.　Our findings show that treatment with FR70 induced regulatory cells and inhibited cytotoxic T cell proliferation, which led to long-term acceptance of mouse cardiac allografts. These findings highlight the potential role of anti-CD70 antibodies as a clinically effective treatment for allograft rejection.